Dietary Behaviour Patterns in Rural Primary Schools: An Empirical Assessment - Anna S. KOWALSKA; Klaudia PASKUDZKA (Communications of International Proceedings, 2025)
The study investigates the extent to which selected demographic factors- age and sex- shape dietary behaviours among students aged 11– 14. Existing research on nutritional practices in early adolescence highlights the importance of demographic determinants; however, empirical findings remain inconclusive, particularly in the context of Central and Eastern Europe. This gap is relevant given the growing emphasis on the role of school food environments in promoting healthy eating. To address this void, the study employs a quantitative survey conducted among students from primary schools, focusing on behaviours directly linked to everyday nutritional routines. Descriptive statistics and chi-square tests were applied to examine patterns related to the number of meals consumed, the frequency of bringing a second breakfast, participation in school lunches, and the use of school shops. The analysis shows that neither age nor sex significantly differentiates the total number of meals or the number of hot meals consumed. No significant associations were identified for bringing a second breakfast, eating school lunches, or using school shops. The only statistically significant relationship was found between bringing a second breakfast and participation in school lunches, although the effect size was weak. Overall, the findings indicate that dietary behaviours in this age group remain relatively stable across demographic categories, suggesting that effective interventions should target school-level determinants rather than demographic segmentation.
Keywords: dietary behaviours; school nutrition; adolescents; school food environment.